DEVELOPMENT OF INSTRUMENTS FOR ASSESSING STUDENT POLITENESS - Rabiatul Adawiah; Mariatul Qibtiah (Indonesian Journal of Educational Development (IJED), 2023)
The purpose of this study was to create and develop an instrument for assessing student politeness that was appropriate and tested for validity and reliability. The method used in this research was Research and Development (R&D). This research was conducted at SMA Negeri 1 Gambut, Banjar Regency, South Kalimantan, with a random sample of 200 people. The data collection technique was in the form of a questionnaire using the Google Form application. To produce an instrument for assessing the politeness of quality students, a validation test was first carried out which was carried out by three experts, namely one linguist, and two education practitioners, namely the Civics teacher and the Counseling Guidance teacher. Data analysis used the SPSS version 23 program. Through the Product Moment test, 18 valid instruments were obtained (rcount value was 0.138 > rtable) with very high reliability value category (with cronbach's alpha 0.96 α (0.6)). Thus, the 18 items of the instrument had the eligibility to assess the polite attitude of students, especially at Peat State High School, Banjar Regency, South Kalimantan.